The Influence Of Local Content Towards The Sales Of SMEs Product Through Media Of Market Place - Yuli Sintha ASI; Ariefah SUNDARI; Hari SUSANTO (Journal of Tourism Economics and Policy, 2022)
The transformation from traditional marketing into digital marketing brings changes to all aspects of human life, including economic aspects for  Micro, Small and Medium Enterprises. Local SMEs fail to compete because the product is not really well-known and is not marketed digitally. The digitalization era forced  SMEs to use social media for promotion. On the contrary, East Kotawaringin Regency SMEs are primarily unfamiliar with digital marketing. As a consequence, many SMEs are not able to survive. This research is carried out to help SMEs survive this Covid-19 disaster by implementing Digital Marketing to see how vital the SME sector is for regional income. It is a quantitative study to know the influence of selling products through the marketplace and how the local cultural content of the product influences the sales increase. The total population is 83  SMEs aged 18 to 25 years. The population is depreciated according to age, culinary sector and education. It obtained 31 samples. Questionnaires are distributed for data collection and are analyzed with SPSS 16. The finding of this research is that there is a correlation between local content in social media toward sales increase, as the independent shown by the t-count for each item is higher  < 0.05. SMEs promote their products on social media based on local culture content linked to a local government website or other businesses such as hotels and tourist attractions.